Implementation of RedCap data systems in Kenyan psychiatric rehabilitation: a community case study - Patel, Neal; Turissini, Matthew; Jaguga, Florence; Barasa, Julius; Okeyo, Lily; Kimaiyo, Mercy; Kosgei, Gilliane; Kipkorir, Naomi; Kwobah, Edith Kamaru (Frontiers in Psychiatry, 2025)
Data collection systems are vital in implementation of interventions within patient care as they allow us to better understand and improve the care given. This is equally true in the field of psychiatric rehabilitation, which has been steadily growing in the medical world for the past 20 years. It has recently been a focus of psychiatric medicine in Kenya with the Kenya Mental Health Action Plan 2021-2025 calling for improvement of care in the field. With psychiatric rehabilitation growing in low- and middle-income countries in recent years studies have come out showing the effects of newly employed programs and stressing the need for data collection practices that can be used to encourage best practices in local communities. This paper describes the implementation of data systems for the Moi Teaching and Referral Hospital Nawiri Skills and Recovery Centre (Nawiri) in Eldoret, Kenya. The goals of the data systems were 1) To collect and organize information for continuous quality improvement of services at Nawiri, 2) To collect information for reporting to MTRH leadership, Ministry of Health as well as private funders, 3) To provide data to assess outcomes of people who receive services at Nawiri to create evidence for effective interventions to help create policy to make psychiatric rehabilitation more available to people living with Severe mental illness in Kenya. Lessons learned from data systems implementation included insights into ease of data collection, adaptability of data instruments to fit facility needs, and ability to reproduce RedCap data collection in other settings.